Lateral variation doped wide bottom trench gate IGBT for reduced on-resistance with improved gate charge. (2021) - Vaidya, Mahesh; Naugarhiya, Alok; Verma, Shrish
Abstract: In this paper, novel concept of lateral variation doping profile in the drift region for IGBT is presented. The variation profile divides the drift region in four sections in such a way that highly doped p + and n + pillars are present at the center, while pillars with lesser concentration are situated at the drift region boundary. Higher concentration below the channel region, enables the presence of more free charges in the conduction path thereby reducing the specific resistance (Ron.A) in the conduction path. The p - and n - section reduces the critical electric field at the corner and maintains the similar breakdown voltage in comparison with the conventional design despite of higher concentration doping profile at the middle. Proposed structure offers 19% improvement in current density and 16% reduction in Ron.A. Lateral variation doped structure also able to reduce on-state voltage drop (Von) by 15.38%. Along with the lateral doping concept, Proposed structure utilizes the broad oxide at the gate region in order to improve the switching performance. The increment in the oxide thickness reduces the gate to collector capacitance (CGC ) and leads to reduces the gate to collector charge (QGC ) by 30%. Reduction in gate charge also improve the switching performance of the devices and reduces the energy losses during the turn-off period. The 20% improvement in turn-off losses at same on-state voltage drop is observed. Additionally, 5% improvement in the on-state voltage drop is also achieved. Additionally, various figure of merit (FOM) is also evaluated. The Baliga's FOM and industrial FOM is improved by 19% and 55% respectively as compared to conventional design.